Thoracotomy in children: A decade review of indications and outcomes - Ezekiel Olayiwola Ogunleye; Olugbenga Oluseyi Olusoji; Oyebola Olubodun Adekola (Journal of Clinical Sciences, 2023)
Background: Thoracotomy in children is relatively rare compared to adults. It can be very challenging due to the peculiar anatomy and physiology in this age group. The objective of the study was to study the indications, outcomes, and complications following thoracotomy. Methods: This was a retrospective analysis of the medical charts of neonates, infants, and children who had undergone thoracotomy under general anesthesia from January 2011 to December 2020 at our institution. Furthermore, we searched for the childhood thoracic diseases necessitating thoracotomy; the indications and complications following thoracotomy, as well as, the quality of life following thoracotomy. The children had either posterolateral or lateral thoracotomy, which spared the latissimus dorsi and/or serratus anterior. Data collected included demographics, surgical intervention, duration of intensive care unit admission, postoperative complications, and clinical outcome. Results: Out of the 39 patients, a majority were female 20 (51.3%), the most common indication for thoracotomy was congenital anomalies in 25 (64.1%) patients (lung malformations, 35.9% and patent ductus arteriosus, 28.2%), followed by foreign body aspiration (20.21%). Postoperative complications were seen in 15 (38.5%), out of whom 3 (20%) had atelectasis, chylothorax in 1 (6.7%), and wound dehiscence in 2 (13.3%). The 30-day mortality was 12.8%. The quality of life as assessed by Karnofsky performance status within 6–12 months after discharge in 32 children was 100 and in two patients (90). Conclusion: The most common indication and complication following thoracotomy at our institution was congenital anomalies in 25 (64.1%) patients (lung malformations, 35.9% and patent ductus arteriosus, 28.2%), and atelectasis, respectively. The 30-day mortality after thoracotomy was 12.8%.